2018
DOI: 10.1002/jccs.201700284
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Methanol Behavior at the Designed Electrochemical Sensor based on Ni(II) Complex and Graphene Nanosheets

Abstract: In this work, the electrochemical oxidation of methanol was investigated by different electrochemical methods at a carbon paste electrode (CPE) modified with (N‐5‐methoxysalicylaldehyde, N´‐2‐hydroxyacetophenon‐1, 2 phenylenediimino nickel(II) complex (Ni(II)–MHP) and reduced graphene oxide (RGO), which is named Ni(II)‐MHP/RGO/CPE, in an alkaline solution. This modified electrode was found to be efficient for the oxidation of methanol. It was found that methanol was oxidized by the NiOOH groups generated by fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Graphene, one of the allotropes of carbon, is two‐dimensional monolayers of carbon atoms arranged in a honeycomb lattice that can be functionalized easily with acidic moieties to give new materials that can be used in acid‐catalyzed processes . It possesses unique physical properties, such as high thermal and electronic conductivity, high thermal stability, and high structural strength, and therefore has diverse applications in various fields such as electrochemical sensors, composite materials, and energy technology . Graphene is easily produced from graphene oxide (GO) by reduction using reducing agents such as NaBH 4 or hydrazine .…”
Section: Introductionmentioning
confidence: 99%
“…Graphene, one of the allotropes of carbon, is two‐dimensional monolayers of carbon atoms arranged in a honeycomb lattice that can be functionalized easily with acidic moieties to give new materials that can be used in acid‐catalyzed processes . It possesses unique physical properties, such as high thermal and electronic conductivity, high thermal stability, and high structural strength, and therefore has diverse applications in various fields such as electrochemical sensors, composite materials, and energy technology . Graphene is easily produced from graphene oxide (GO) by reduction using reducing agents such as NaBH 4 or hydrazine .…”
Section: Introductionmentioning
confidence: 99%
“…It is of crucial importance to ensure both even dispersion and good electron transfer between the surface of NPs and electrode to get higher sensitivity and lower detection limit. Typically, some inorganic–inorganic, organic–organic, inorganic–organic configurations have been proposed such as palladium–nickel/silicon nanowires (Pd–Ni/SiNWs); 22 NiO/Fe 2 O 3 ; 23 Au–Ni/graphene oxide; 24 graphene–NiO nano composites; 25 polymethyl methacrylate–graphene–carbon nanotubes; 26 reduced graphene oxide/ferricyanide; 27 N -5-methoxysalicylaldehyde, N ′-2-hydroxyacetophenone – 1,2 phenylenediimino nickel( ii ) (Ni( ii )–MHP) and reduced graphene oxide (RGO) (Ni( ii )–MHP/RGO); 28 EG/rGO/np–NiOOH; 29 PTh-α-Fe 2 O 3 30 … Although Pt and Pt-based catalysts are common and efficient for MeOH oxidation, there are some significant obstacles preventing their large-scale application such as high cost, reactivity, and the extent of poisoning towards MeOH.…”
Section: Introductionmentioning
confidence: 99%
“…[21,22] Due to excellent electrical conductivity, two-dimensional single-layer crystal lattice, high mechanical strength, large surface area, low cost, and simple fabrication routes, graphene serves as a platform for the MOFs' catalyst, [23,24] and electrochemical sensors. [25][26][27][28][29][30] Herein, to prevent agglomeration of graphene sheets and to improve the electrochemical sensors' performance, the rGO was functionalized with a polypyrrole (PPy) due to its environmental stability, high electrical conductivity, and facile preparation. Earlier works have indicated that the catalyst system, based on conducting polymer such as PPy along with carbon support such as GO, leads to enhanced conductivity, active surface area, and electrochemical cyclability.…”
Section: Introductionmentioning
confidence: 99%